MODIFIED APPROACH TO THE DIAGNOSIS OF PYELONEPHRITIS IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Pyelonephritis is the second most common disease in children after acute respiratory infections, between which there is a clear and close relationship. Objective. Determination of clinical and laboratory features of early diagnosis of pyelonephritis in children who have had COVID-19. Methods. A cohort retrospective clinical follow-up of 121 children with pyelonephritis was carried out. Results and discussion. An analysis of changes in the partial function of the kidneys in all patients with pyelonephritis was carried out. The results of the study indicate that in patients of groups 1 and 3, all the studied clinical and laboratory parameters were significantly impaired compared to group 2. These changes confirm the possibility of their different severity depending on the causes of the disease (etiological factors). Conclusion. In patients with pyelonephritis who had COVID-19, damage was found not only to the proximal (proteinuria increased by 11 times compared to healthy children) and distal tubules (ammoniogenesis function decreased by 34%) of the renal nephrons, but also to the glomeruli (GFR decreased by 38% compared to healthy children), which is atypical for pyelonephritis in children without a history of COVID-19.